POTENCY AND PROBLEMS OF COASTAL REGION DEVELOPMENT IN WEST BORNEO - Sudrajat, Jajat (Jurnal Social Economic of Agriculture, 2013)
The development of coastal region in West Borneo have basic problem, that is: first, many household are still poor. The second, there is deterioration of environmental quality. This conceptual study is intended to describe some problems of coastal region development and also try to formulate alternative strategy which can be done. Although its natural resources is very rich which is indicated by slope slightly of coastal and type of land is enough fertile, but some classical problems still occur, that is: a) still many communities are isolated, and b) social structure of community indicated to social polarization (two class community). Based on these features, so that some development strategy can be formulated, that is: (1) for isolated rural communities, the development strategy which can be done, is combine the participative and welfare strategy, and (2) for coastal rural, is suggested to do comprehensive strategy which is combine three development strategy, that is growth, welfare, and participative strategy. To increase income of fisherman needs to diversification source of income, not only on fisheries and agriculture but also non farm sector. Keywords: coastal region, development, development strategy